Characterization of the Bacterial Community Associated with Larvae and Adults of Anoplophora chinensis Collected in Italy by Culture and Culture-Independent Methods. (27th August 2013) - Rizzi, Aurora; Crotti, Elena; Borruso, Luigimaria; Jucker, Costanza; Lupi, Daniela; Colombo, Mario; Daffonchio, Daniele
Abstract : The wood-boring beetle Anoplophora chinensis Forster, native to China, has recently spread to North America and Europe causing serious damage to ornamental and forest trees. The gut microbial community associated with these xylophagous beetles is of interest for potential biotechnological applications in lignocellulose degradation and development of pest-control measures. In this study the gut bacterial community of larvae and adults of A. chinensis, collected from different host trees in North Italy, was investigated by both culture and culture-independent methods. Larvae and adults harboured a moderately diverse bacterial community, dominated by Proteobacteria, Actinobacteria, and Firmicutes. The gammaproteobacterial family Enterobacteriaceae (genera Gibbsiella, Enterobacter, Raoultella, and Klebsiella ) was the best represented. The abundance of such bacteria in the insect gut is likely due to the various metabolic abilities of Enterobacteriaceae, including fermentation of carbohydrates derived from lignocellulose degradation and contribution to nitrogen intake by nitrogen-fixing activity. In addition, bacteria previously shown to have some lignocellulose-degrading activity were detected at a relatively low level in the gut. These bacteria possibly act synergistically with endogenous and fungal enzymes in lignocellulose breakdown. The detection of actinobacterial symbionts could be explained by a possible role in the detoxification of secondary plant metabolites and/or protection against pathogens.